2021
DOI: 10.1002/jcsm.12702
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic impact of muscle and fat mass in patients with heart failure

Abstract: Background Cachexia, characterized by loss of muscle with or without loss of fat mass, is a poor prognostic factor in patients with heart failure (HF). However, there is limited investigation on the prognostic impact of muscle and fat mass separately in HF. We hypothesized that muscle and fat mass have different effects on the prognosis of HF. Methods This was an observational cohort study of 418 patients (59% were men) admitted with a diagnosis of HF (71 ± 13 years [mean ± standard deviation]), with left vent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 43 publications
0
34
0
Order By: Relevance
“…Recently, Konishi et al have clearly showed low MM defined by DEXA was associated with prognosis independent of other prognostic factors. 23 In contrast, a study that evaluated the MM of 359 outpatients with HF with BIA showed that low MM was not associated with mortality independent of other covariates. 24 Although these studies have not simultaneously evaluated MM using BIA and DEXA and did not compare their prognostic predictability, these findings are consistent with our study results.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Recently, Konishi et al have clearly showed low MM defined by DEXA was associated with prognosis independent of other prognostic factors. 23 In contrast, a study that evaluated the MM of 359 outpatients with HF with BIA showed that low MM was not associated with mortality independent of other covariates. 24 Although these studies have not simultaneously evaluated MM using BIA and DEXA and did not compare their prognostic predictability, these findings are consistent with our study results.…”
Section: Discussionmentioning
confidence: 95%
“…Recently, Konishi et al . have clearly showed low MM defined by DEXA was associated with prognosis independent of other prognostic factors 23 . In contrast, a study that evaluated the MM of 359 outpatients with HF with BIA showed that low MM was not associated with mortality independent of other covariates 24 .…”
Section: Discussionmentioning
confidence: 97%
“…Firstly, this is the first large-scale, nationwide study to assess the association between body composition and mortality among HF patients. To date, only a limited number of studies have examined this relation, and the findings were inconsistent (16)(17)(18)(19). Although these studies used a direct measurement of body composition, the lack of statistical power that resulted from the small sample size (198-418 patients) makes it impossible to draw firm conclusions.…”
Section: Discussionmentioning
confidence: 99%
“…Direct measurement of body composition is high-cost and requires sophisticated technologies, which limits its utilization in clinical practice. Therefore, to date, few studies, with relatively small sample size, have reported the effect of body composition among HF patients (16)(17)(18)(19). There is a need to evaluate this association in a large population to assure adequate statistic power.…”
Section: Introductionmentioning
confidence: 99%
“…Many factors affect the prognosis of NIDCM; these include genetics and family history, aetiology, gender, age, and presence of comorbidities such as renal failure, chronic obstructive pulmonary disease, etc. 5 9 . Several of these factors are of high predictive value for the prognosis of NIDCM 10 .…”
Section: Introductionmentioning
confidence: 99%